1978
DOI: 10.1007/bf01246957
|View full text |Cite
|
Sign up to set email alerts
|

Absence of ?cheese effect? during deprenyl therapy: Some recent studies

Abstract: Although the selective monoamine oxidase (MAO) B inhibitor, (-)deprenyl, has been shown to be free from the "cheese effect" in man after tyramine challenge, the reason for this is far from clear: it may well be independent of the selective inhibitory action of the drug, for during chronic administration there is some evidence to suggest that both A and B forms of the enzyme are equally inhibited. By-passing the putative MAO A gut barrier in the pig (chosen because it possesses MAO B alone in all other tissues)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…The protective effects of ASA and meloxicam are not related to alterations of MPTP conversion to MPP ϩ or to alterations in MPP ϩ uptake, because striatal MPP ϩ levels were not significantly different between the MPTP-treated acetylsalicylic acid, meloxicam, and saline groups. In the present study, only selegiline-treated controls showed significantly decreased MPP ϩ tissue levels, due to its wellknown MAO-B inhibition (Sandler et al, 1978). The aromatic ring of ASA and salicylic acid easily reacts with hydroxyl radicals and therefore part of the neuroprotective effects may be mediated by their direct radical scavenging properties (Ferger et al, 1999).…”
Section: Discussionmentioning
confidence: 78%
“…The protective effects of ASA and meloxicam are not related to alterations of MPTP conversion to MPP ϩ or to alterations in MPP ϩ uptake, because striatal MPP ϩ levels were not significantly different between the MPTP-treated acetylsalicylic acid, meloxicam, and saline groups. In the present study, only selegiline-treated controls showed significantly decreased MPP ϩ tissue levels, due to its wellknown MAO-B inhibition (Sandler et al, 1978). The aromatic ring of ASA and salicylic acid easily reacts with hydroxyl radicals and therefore part of the neuroprotective effects may be mediated by their direct radical scavenging properties (Ferger et al, 1999).…”
Section: Discussionmentioning
confidence: 78%
“…The decreased response to L-Dopa and the appearance of "on-off effect" are thought to be related to the obvious progression of the disease (Barbeau, 1976;Castaigne et al, 1976;Duvoisin, 1974;Birkmayer et al, 1979;Rinne et aL, 1976;Yahr, 1978). The continuous excessive supply of exogenous L-Dopa may account for the alterations in the properties of the central nervous system DA-receptor and is thought to be involved in the mechanism of the "on-off effect" (Castaigne, 1976;Hornykiewicz, 1973;Sandler et aL, 1978;Seernan et al, 1978;Yahr, 1978). The application of various decarboxylase-inhibitors (Barbeau et al, 1971;Fahn, 1974;Rinne et al, 1976;Wajsbort et aL, 1978;Wajsbort et aL, 1971), the imposition of dietary protein restrictions (Cotzias et aL, 1973;Papavasiliou et al, 1974;Wajsbort, 1977) or even administration of sustained release L-Dopa preparations (Woods et al, 1973) can be successful in the treatment of many cases of Parkinsonism, but they are only partially helpful in "on-off effect".…”
Section: Introductionmentioning
confidence: 97%
“…Tyramine escaping enzymatic degradation in the intestinal wall undergoes mainly MAO-B catabolism in the liver (Youdim et al 1979). Consistent with the predominance of MAO-A enzymes in the intestinal mucosa and sympathetic nerve endings, MAO inhibitors which are selective for MAO-B over MAO-A do not appear to significantly enhance the pressor response to oral tyramine (Lees et al 1977;Da Prada et al 1990;Finberg and Youdim 1985;Sandler et al 1978;Youdim 1990;Youdim and Weinstock 2004;Youdim 1977). Most currently available MAO inhibitors are rather specific towards MAO-B, but some of them are irreversible inhibitors.…”
Section: Introductionmentioning
confidence: 52%